2011
DOI: 10.1007/s00586-010-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical outcomes of cervical spondylotic myelopathy in patients aged 80 years or older: a multi-center retrospective study

Abstract: With the aging of the population in developed countries, spine surgeons have recently been more likely to encounter elderly patients in need of treatment. This study investigated whether decompression surgery for cervical spondylotic myelopathy (CSM) in elderly patients aged 80 years or older would likely be a reasonable treatment. We retrospectively reviewed 605 consecutive patients with cervical myelopathy who underwent decompression surgery between 2004 and 2008. Patients with other conditions that could af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 19 publications
1
38
2
5
Order By: Relevance
“…Some authors have reported that surgical outcomes in elderly patients are worse than those in younger patients [1,12,13]. While irreversible functional deficits arising from a damaged spinal cord may occur in elderly patients, several recent articles have reported that elderly patients can achieve a reasonable degree of recovery after decompression surgery [14,15]. We speculated that this controversy may have resulted from a difference in the severity of CSM symptoms and total pre-operative neurological impairment between younger and elderly individuals, in addition to differences in objective measurements among various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that surgical outcomes in elderly patients are worse than those in younger patients [1,12,13]. While irreversible functional deficits arising from a damaged spinal cord may occur in elderly patients, several recent articles have reported that elderly patients can achieve a reasonable degree of recovery after decompression surgery [14,15]. We speculated that this controversy may have resulted from a difference in the severity of CSM symptoms and total pre-operative neurological impairment between younger and elderly individuals, in addition to differences in objective measurements among various studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have recommended surgical decompression for the treatment of CCM [1,7,10]. Although the ''best practice'' approach to the treatment of CCM remains controversial, for patients with both kyphosis and ventral compression the use of a ventral surgical approach may be the most beneficial [6,23].…”
Section: Discussionmentioning
confidence: 99%
“…Nagashima et al compared 37 patients with CSM >80 years old and 124 patients <80 years old in a multicenter retrospective study and found that lower Japanese orthopaedic association scores before and after surgeries were observed in the elder group, but age was not significantly associated with recovery rate or surgical and general complications 24) . A study of patients with CSM who underwent decompressive surgery in a single institution compared 36 patients !…”
Section: Discussionmentioning
confidence: 99%